La gestión de residuos en la empresa: motivaciones para su implantación y mejoras asociadas - Unai Tamayo Orbegozoa; María Azucena Vicente Molinaa; Julen Izaguirre Olaizolab (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
– Nowadays the reduction or elimination of waste has become a major environmental concern among industrialized countries and a priority for companies. In this work it is carried out a review of the postulates of the classical economic model, existing until a few dates, in connection with the variable environment and waste generated by firms. It is also examined the literature about the potential of the waste management and possible alternatives for obtaining of advantages or benefits derived from an efficient treatment of waste. This paper is completed with an empirical analysis of the waste management in companies of the Basque Autonomous Community. The motivations that drive firms to implement a waste management system and the advantages or benefits which derive from this fact are analyzed among other factors.
Keywords: K32; Q20; Q50; 650; waste management; environmental management; environmental management system; ISO 14001; motivations; improvement